People in harm's way - Rentschler, Jun,Salhab, Melda (World Bank Group, Climate Change Group & Global Facility for Disaster Reduction and Recovery, 2020)
Flooding is among the most prevalent natural hazards affecting people around the world. This study provides a global estimate of the number of people who face the risk of intense fluvial, pluvial, or coastal flooding. The findings suggest that 1.47 billion people, or 19 percent of the world population, are directly exposed to substantial risks during 1-in-100 year flood events. The majority of flood exposed people, about 1.36 billion, are located in South and East Asia; China (329 million) and India (225 million) account for over a third of global exposure. Of the 1.47 billion people who are exposed to flood risk, 89 percent live in low- and middle-income countries. Of the 132 million people who are estimated to live in both extreme poverty (under
10.1596/1813-9450-9447
Keywords: Graue Literatur; Flood; exposure; disaster; poverty